Doing transgender 'right': Bodies, eroticism and spirituality in khwajasira work. (February 2023) - Ashraf, Muhammad Junaid; Pianezzi, Daniela; Awan, Muhammad Aqeel
The regulative and oppressive effects of gender norms on bodies of transgender workers have been mostly explored in standard binary gender work settings. We explore the regulative effects of specialized transgender work regimes by posing the following two questions: how do specialized transgendered work regimes regulate transgender work and bodies? and how do transgender workers cope with these regimes? Through a case study of khwajasiras, a community of male-to-female transgender people in Pakistan, we explain how competing and conflicting body ideals of hyper-eroticism, spirituality, and hybridity set by these regimes, allow khwajasiras to transgress the binary gender norms. Ironically, however, these specialized work regimes have their own regulative and oppressive effects on khwajasiras ' bodies and work. We then demonstrate how khwajasiras cope with these regulative effects in three different ways: embracing the body ideals, strategically shifting work and body across the regimes, and relegating body norms as unimportant for being a transgender. We finally argue that these differences in enacting different form of transgenderness is an outcome of a tight coupling or contradiction between audiences, khwajasira community and individual workers' own sense of transgender authenticity.